A BCWD-resistant line of rainbow trout exhibits higher abundance of IgT+ B cells and heavy chain tau transcripts compared to a susceptible line following challenge with Flavobacterium psychrophilum. (September 2017) - Zwollo, Patty; Hennessey, Erin; Moore, Catherine; Marancik, David P.; Wiens, Gregory D.; Epp, Lidia
Abstract: Bacterial Cold Water Disease (BCWD) is a common, chronic disease in rainbow trout, and is caused by the gram-negative bacterium Flavobacterium psychrophilum (Fp) . Through selective breeding, the National Center for Cool and Cold Water Aquaculture has generated a genetic line that is highly resistant to Fp challenge, designated ARS-Fp-R (or R-line), as well as a susceptible "control" line, ARS-Fp-S (S-line). In previous studies, resistance to Fp had been shown to correlate with naive animal spleen size, and further, naïve R-line trout had been shown to have a lower abundance of IgM + and IgM ++ cells compared to S-line fish. Here we wished to first determine whether the abundance of IgT + and/or IgT ++ cells differed between the two lines in naïve fish, and if so, how these patterns differed after in vivo challenge with Fp . Fp challenge was by intramuscular injection of live Fp and tissue collections were on days 5, 6, and/or 28 post-challenge, in two independent challenge experiments. Flow cytometric and gene expression analyses revealed that naïve R-line fish had a higher abundance of IgT + B cells in their anterior kidney, spleen, and blood, compared to S line fish. Further, that after Fp challenge, this difference was maintained between the two lines. Lastly, abundance of IgT + B cells and expression of secHCtau correlated with lower Fp pathogen loads in challenged fish. In the anterior kidney, IgM + B cell abundance correlated with increased Fp loads. Together, these results suggest that IgT + B lineage cells may have a protective function in the immune response to Fp. Highlights: A genetic line of rainbow trout resistant to Flavobacterium psychophilum has a higher abundance of IgT+ B cells compared to a susceptible control line both before and after bacterial challenge. Higher abundance of IgT+ B cells and expression of secHCtau correlated with lower pathogen loads in challenged fish. The data suggest that IgT+ B lineage cells may have a protective function in the immune response to Fp.